(untitled) (International Journal of Engineering and Computer Science, 2014)
The Ophthalmic diseases lack fatality, but have tendency to progress overtime (morbidity) and have more impact on daily life of the patients. Diseases like Glaucoma and Diabetic Retinopathy have chronic course which can be sight-threatening if not intervened in due course and proper follow-up. The diagnosis in such diseases, require examinations by optometry instruments following the symptoms. An integrated interpretation of these examination results are needed as they have different representation and their significance, to reach final diagnosis. Currently this interpretation is dependent on individual attributes such as, past experience and domain knowledge of the expert. Thus there arises a need of automated diagnosis free from individual attributes and can produce integrated interpretation. This paper proposes an Intelligent Agent Based Model for diagnosis of ophthalmologic diseases. The intelligent agents of the model are specialized and use advance computational techniques for deriving diagnosis from numerical data and images, thus combines autonomy and communicative characteristics of agents to reach to a final diagnosis.